An introduction to psycholinguistics - Steinberg, Danny D.; Sciarini, Natalia V. (London : Pearson/Longman, 2006)
An Introduction to Psycholinguistics examines the psychology of language as it relates to learning, mind and brain as well as to aspects of society and culture. How do we learn to speak and to understand speech? Is language unique to humans? Does language influence culture? Using non-technical language, and providing concrete examples, the authors explore: How children learn to speak and read their native language; Deaf language education; Case studies of wild children and animals and what we can learn from these; Second language acquisition, second language teaching methods, and the problems associated with bilingualism; Language and the brain; The relationship between thought and language. In this new edition the authors propose a radical new theory of grammar -- natural grammar -- which unlike other theories can account for both speech comprehension and speech production. Also taking into account the extensive growth in theory, research and practice, this new edition is an accessible and focused introduction to the key issues and the latest research in the field of psycholinguistics. - Back cover.
First-language learning. How children learn language -- The deaf and language: sign, oral, written -- Reading principles and teaching -- Wild and isolated children and the critical age issue for language learning -- Animals and language learning -- Second-language learning. Children vs. adults in second-language learning -- Second-language teaching methods -- Bilingualism, intelligence, transfer, and learning strategies -- Language, mind and brain. Language, thought and culture -- Where does language knowledge come from? Intelligence, innate language ideas, behaviour? -- Natural grammar, mind and speaker performance -- Language and the brain.
Includes bibliographical references (pages 263-293) and indexes.
Keywords: Psycholinguistics; Psycholinguistics